Effect of cannabinoids on platelet serotonin uptake - Velenovská, Marie; Fisar, Zdenek (Addiction biology, 2007)
Serotonin is involved in many of the same processes affected by cannabinoids; therefore, we investigated in vitro and in vivo effects of these drugs on the function of serotonin transporter. The effect of Delta(9)-tetrahydrocannabinol (Delta(9)-THC), endocannabinoid anandamide and synthetic cannabinoid receptor agonist WIN 55,212-2 on platelet serotonin uptake and membrane microviscosity was examined in 19 marijuana smokers and 20 controls. (1) Serotonin uptake was inhibited at higher doses of Delta(9)-THC (IC(50) = 139 micromol/l), anandamide (IC(50) = 201 micromol/l) or WIN 55,212-2 (IC(50) = 17.4 micromol/l); the inhibition was found non-competitive. Delta(9)-THC, anandamide and WIN 55,212-2 produced different effects on the membrane microviscosity. (2) Maximal velocity of platelet serotonin uptake was significantly increased in a group of chronic marijuana smokers suffering impairment of cognitive functions when compared with controls. Opposite effect of marijuana smoking on the serotonin uptake efficiency was observed in males beside females. In summary, this study provides evidence that (1) Activity of serotonin transporter is acutely affected by cannabinoids at relatively high drug concentrations; this effect is indirect and can be partially accounted for the changes in the membrane microviscosity. (2) Increase of maximal velocity of the serotonin uptake could be understood as adaptation change in the serotonergic system induced by chronic cannabis use. A hypothesis was supported that lowered serotonin uptake may reflect a gender-related differences in effects of psychoactive cannabinoids.
Keywords: buněčná membrána; imipramin; Morpholines; morfoliny; techniky in vitro; Humans; Naphthalenes; Dronabinol; Serotonin Plasma Membrane Transport Proteins; kyseliny arachidonové; Serotonin; polynenasycené alkamidy; kanabinoidy; serotonin; viskozita; Dose-Response Relationship, Drug; Female; naftaleny; Marijuana Smoking; trombocyty; dospělí; endokanabinoidy; Endocannabinoids; Viscosity; lidé; Benzoxazines; kouření marihuany; kokain; tetrahydrokanabinol; Adult; Blood Platelets; Imipramine; ženské pohlaví; Male; membránové transportní proteiny pro serotonin; Sex Characteristics; Cocaine; benzoxaziny; Cannabinoids; In Vitro Techniques; pohlavní dimorfismus; vztah mezi dávkou a účinkem léčiva; Cell Membrane; mužské pohlaví; Polyunsaturated Alkamides; Arachidonic Acids